The Influence of Firm Ecological Recruitment Advertisements On Organizational Attractiveness and Career Choices: An Experimental Research - Jatmiko, Pracoyo Budi (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2004)
This present study investigates college studentsâ interest to a green company and intention to work for the company. This study also investigates how much salary they are willing to receive to work for the company. The results of the study show construct validity evidence that being attracted to the organization and desire to pursue a job in the organization are divergence constructs. Both constructs are influenced by different factors in magnitude. This study also finds that environmental information stated in the recruitment brochure can positively influence applicantsâ interest and intention to pursue a job in the company. Yet, applicants only react positively to an environment-friendly company that offers high pay level. They are more attracted to an environment-friendly company that offers high pay level. However, this relationship does not influence applicantsâ intention to pursue a job. Applicantsâ personal concern on the environment do not influence applicantsâ interest and intention to pursue a job in a green company. This suggests that a positive environmental information articulated in the recruitment brochure could positively affect potential recruits, even when applicants did not personally see herself or himself as being particularly pro-environment.